2007
DOI: 10.1590/s0100-879x2006005000171
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and toxicology of diphenyl diselenide in several biological models

Abstract: The pharmacology of synthetic organoselenium compounds indicates that they can be used as antioxidants, enzyme inhibitors, neuroprotectors, anti-tumor and anti-infectious agents, and immunomodulators. In this review, we focus on the effects of diphenyl diselenide (DPDS) in various biological model organisms. DPDS possesses antioxidant activity, confirmed in several in vitro and in vivo systems, and thus has a protective effect against hepatic, renal and gastric injuries, in addition to its neuroprotective acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…Alternatively, in the absence of an excess of a low molecular weight reducing thiol, TrxR can reduce ebselen and/or ebselen diselenide using reducing equivalents from NADPH [10,11]. Diphenyl diselenide and analogs share several antioxidant and neuroprotective properties with ebselen [5,[19][20][21][22][23][24][25][26] and they are also mimetics of native GPx enzyme [5,8]. However, there is a dearth of information in the literature indicating that simple diorganyl diselenides such as diphenyl diselenide and its analogs can be substrates for TrxR.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, in the absence of an excess of a low molecular weight reducing thiol, TrxR can reduce ebselen and/or ebselen diselenide using reducing equivalents from NADPH [10,11]. Diphenyl diselenide and analogs share several antioxidant and neuroprotective properties with ebselen [5,[19][20][21][22][23][24][25][26] and they are also mimetics of native GPx enzyme [5,8]. However, there is a dearth of information in the literature indicating that simple diorganyl diselenides such as diphenyl diselenide and its analogs can be substrates for TrxR.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, the interest in developing synthetic organic selenium compounds has increased considerably, because some of these compounds present chemical and biological antioxidant properties [21][22][23][24][25][26]. The antioxidant and neuroprotective properties of diphenyl diselenide (PhSe) 2 , a structurally simple organoselenium compound, against ischaemia and MeHg-induced toxicity have been described [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…7 In contrast, studies have shown that DPDS has pro-oxidative effects in vivo, such as oxidation of sulfhydryl (-SH) groups in proteins, reduction of glutathione levels (GSH), and inhibition of δ-aminolevulinic acid dehydratase (δ-ALA-D). 8 In addition, the lethal dose (LD 50 ) for a single intraperitoneal (ip) administration of DPDS in mice is 210 µmol/kg. In this regard, nanotechnology is widely applied to produce significant advantages over prodrugs, including improving the bioavailability of lipophilic molecules and increasing the safe dose of toxic compounds.…”
Section: Introductionmentioning
confidence: 99%